PHYSICAL AND CHEMICAL COMPOSITION OF SOILS OF THE FEDERAL NATURE RESERVE “KHARBINSKY” - Aleksey A. Buluktaev (Ûg Rossii: Èkologiâ, Razvitie, 2019)
Aim. This article discusses the current state of the chemical composition of the soils of the Kharbinsky federal nature reserve located on the territory of Yustinsky and Yashkulsky districts of the Republic of Kalmykia. The predominant soil compositions of the reserve are complexes of brown semi-desert soils with saline and sands. These soils are highly susceptible to erosion, mainly wind. Erosion is facilitated by the light mechanical composition of soils, land use and arid climate where only sparse semi-desert grass stands to grow thus creating no dense turf. Methods. For the general characteristics of the soil, the following analyzes were carried out: analysis of water extraction (the soils were analyzed for Са2+, Mg2+and Na+ cations, НСО3-, CI- and SO42- anions as well as pH), analysis for the content of nitrogen, phosphorus and potassium, as well as the determination of heavy metals. Results. As a result of chemical analysis, it was found that the soils in the settlements are more saline than in the steppe. The studied soils contain little humus, it varies from 0.37 to 4.66%. The nitrogen content in the soil in the reserve varies from 24.5 to 64.8 mg/1000 g. The content of mobile phosphorus in the studied soils varies over a wide range from 14.0 to 150.0 mg/1000 g. The studied soils are insufficiently supplied with exchangeable potassium, the content of which ranges from 0.12 to 1.17 mg/1000 g. Conclusions. As a result of the study, it was established that agricultural activity leads to a change in the chemical composition of the soil: macroelement composition of the soil, type and degree of salinization change; content of heavy metals increases.